School Bulletin Boards as a Contextual Strategy to Enhance Elementary Students’ Numerical Literacy - Damawansyah, Dandi; Haifaturrahman, Haifaturrahman; Nizaar, Muhammad (STIT Ahlussunnah Bukittinggi, 2025)
This study aims to describe the use of school bulletin boards as an effort to improve the numerical literacy of elementary school students. The background of this study stems from the low ability of students to understand numerical concepts contextually in the school environment. This study uses a descriptive qualitative approach, with the research subjects being teachers and students at an elementary school in Surakarta. Data were collected through observation, interviews, and documentation, then analyzed using Miles and Huberman's interactive analysis model. The results show that the use of school bulletin boards can increase students' interest in learning and numerical abilities through the presentation of information based on numbers, graphics, and everyday problems. Furthermore, bulletin boards serve as a collaborative medium that fosters students' creativity and critical thinking skills. This study implies the need for teachers to integrate school media into numerical learning as a contextual literacy strategy based on the learning environment.